Improving Students’ Speaking Achievement by Using Short Movie Media - Dewi Elizabeth S; Sumarsih Sumarsih (Universitas Negeri Medan, 2012)
This research concerns on improving students’ achievement in speaking by using short movie media. The objective was to find out the improvement of students’ achievement in speaking. This research was conducted by using action research method. The subject of the research was XI IPA-1 students of SMA Negeri 8 Medan. The numbers of students were sixteen students. They were taught speaking by using short movie media. The instruments used were diary notes, interview sheets, and observation sheets. In analyzing data, the mean of students’ score for the first competency test was 42,5 for the second competency test was 61,25 and for the third competency test was 85 and the total percentage of improvement from the first competency test to the third competency test was 68,75%. The conclusion is that students’ achievement in speaking can be improved by using short movie media. It is suggested that teachers should apply short movie media as one of media to improve students’ speaking achievement. Key Words: Students’ achievement, Speaking, Short Movie Media